Dietary habits and supplement use of elite adolescent cyclists - Mayho, H.; Nicholas, C.; Mitchell, N. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Diet is key to health and athletic performance. Dietary intake of British Cycling Olympic Development Programme (ODP) athletes was assessed and compared in 1st and 2nd year cyclists. Supplement use of these athletes was also determined. Methods: Forty adolescent cyclists, 25 male and 15 female (mean age 16.2 years) completed a Dietary Habits Questionnaire (DHQ) that included a Food Frequency Questionnaire (FFQ) and questions to assess monthly supplement use. Dietary analysis was conducted with a sample of 21 FFQ, using Microdiet™ software. Supplement use was calculated for all 40 participants. Energy and macronutrient intake was compared to UK dietary reference values (DRVs). Results: ODP cyclists achieved DRVs for energy, carbohydrate and saturated fat (SF), but both males and females consumed more protein than recommended, exceeding DRV by 137.1g and 111.6g respectively (Z-3.180, p=0.001, n=13; Z- 2.521, p=0.012, n=8). Dietary intake of 1st and 2nd year cyclists did not differ. Supplement use did not differ between 1st and 2nd year cyclists ( 2=0.231, df=1, p=0.631) but were used at least once a week by 95% of ODP athletes. Average intake per rider per month was 78.2 items, although there were large range values of total monthly use per rider (0-272). Use was more prevalent in male athletes than females (96 vs. 49 items per month) ( 2=15.234, df=1, p<0.001) and compared to other squads, the sprint athletes (TS) used significantly more (122 vs. 75 (Endurance), 24 (BMX), 77 (MTB)), ( 2=64.60, df=3, p<0.001). The most popular supplements amongst the 40 athletes were protein/recovery drinks, multivitamins, fish oil/omega 3, vitamin C and carbohydrate (CHO) bars. Discussion: Dietary intake appeared to be adequate, but further research is needed using DRVs specific to young athletes. Small improvements in dietary composition appeared in 2nd year athletes although these were not significant. 2nd year athletes consumed more of their total energy from CHO (+1.76%) and protein (+0.82%) and less from fat (-2.45%), suggesting nutrition education may have had a small impact. The high prevalence of supplement use found among these young athletes is consistent with previous findings from young UK athletes from other sports (Petróczi et al., 2008). However, these results are concerning as young athletes are advised against using supplements by the IOC (2011) due to the associated risks. Further research is needed in order to develop an athlete-specific, validated FFQ and also to determine reasons for supplement use.